UKMH Duygusal Zeka Testinin Türkçeye Uyarlanması ve Psikometrik Özelliklerinin İncelenmesi - Tatar, Arkun; Saltukoğu, Gaye; Tok, Serdar; Bender, Merih Tekin (AVES Yayıncılık, 2016)
Amaç: Türkçe az sayıda duygusal zeka ölçeği vardır ve Uluslararası Kişilik Madde Havuzu-Duygusal Zeka Testi (UKMH-DZT), geliştirildiği madde havuzu nedeniyle birçok olumlu yan içermektedir. Bu çalışmada, UKMH-DZT'nin Türkçeye uyarlanması ve psikometrik özelliklerinin incelenmesi amaçlanmıştır. Yöntem: Çalışmaya 18-80 yaş ara-sında 1754 kişi katılmıştır. Bu katılımcıların 18-63 yaşları arasında olan 211'i de test-tekrar test çalışmasına katıl-mıştır. Bulgular: Testin asıl uygulamasında sırasıyla duygulara yaklaşım 0.64, duygu temelli karar verme 0.71, empatik ilgi 0.57, olumsuz ifade edicilik 0.58, olumlu ifade edicilik 0.70, karşılık olarak üzüntü 0.61, karşılık olarak neşe 0.59 ve test bütünü 0.86 alfa iç tutarlılık katsayıları göstermişlerdir. On beş gün sonra yapılan tekrar test uygu-laması ile alt boyutların 0.67-0.80 arasında, test bütünü için de 0.81 test-tekrar test bağıntı katsayıları elde edilmiştir. Testin doğrulayıcı faktör analizi ile test edilen yedi boyutlu tek düzeyli faktör yapısında İyi Uyum İndeksi 0.95, Düzel-tilmiş İyi Uyum İndeksi 0.92, Hata Kareleri Ortalamasının Karekökü 0.03 ve Yaklaşık Hataların Ortalama Karekökü 0.09 bulunmuştur. Madde yanıt kuramı ile yapılan incelemede bazı maddelerin düşük, bazı maddelerin yüksek ayırt edicilik gösterdiği görülmüştür. Sonuç: Bu çalışmayla Türkçe uyarlaması yapılan ölçeğin çok güçlü bir yapısı olma-sa da, geçerli ve güvenilir bir ölçme aracı olduğu gözlenmiştir.

Objective: Turkish emotional intellinge scales are few, and Emotional Intelligence Test (IPIP-EIT) has several favorable features due to its large item pool, International Personality Item Pool, it was developed. The aim of this study is to adopt IPIP-EIT into Turkish and to examine the scale's psychometric properties. Methods: A thousand seven hundred fifty-four people ranging in age from 18 to 80 participated in the study. Out of these participants 211 people ranging in age from 18 to 63 took place in the test-retest study. Results: Alpha internal consistency coefficients of the main application of the test were as follows: 0.64 for attending emotions, 0.71 for emotion based decision making, 0.57 for emphatic concern, 0.58 for negative expressivity, 0.70 for positive expressivity, 0.61 for responsive distress, and 0.59 for responsive joy. Alpha internal consistency coefficient for the entire scale was 0.86. Correlations coefficients between the test and retest scores ranged from 0.67 to 0.80 for the subscales and it was 0.81 for the entire scale. Confirmatory factor analysis of the test showed seven dimensional single level factor structure. Its selected fit indexes were found as follows: goodness of fit index 0.95, adjusted goodness of fit index 0.92, root mean square error 0.003, and root mean square error of approximation 0.09. Examination of items based on item-response theory suggested that while some items had high discriminant power, others had low discriminant power. Conclusion: Results of the present study indicates that even though Turkish adaptation of the IPIP-Emotional Intelligence Test has not a very strong structure, it can be considered as a valid and reliable device to measure emotional intelligence.
Adaptation of Emotional Intelligence IPIP Scales into Turkish and Examination of Its Psychometric Properties
Keywords: UKMH-Duygusal Zeka Testi; Duygusal Zeka; Geçerlilik; Güvenilirlik; Emotional Intelligence IPIP Scales; Emotional Intelligence; Validity; Reliability